2003
DOI: 10.1109/tsp.2003.809368
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of existing and new methods for data hiding with known-host information in additive channels

Abstract: A considerable amount of attention has been lately payed to a number of data hiding methods based in quantization, seeking to achieve in practice the results predicted by Costa for a channel with side information at the encoder. With the objective of filling a gap in the literature, this paper supplies a fair comparison between significant representatives of both this family of methods and the former spread-spectrum approaches that make use of near-optimal ML decoding; the comparison is based on measuring thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
109
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 25 publications
2
109
0
4
Order By: Relevance
“…In paper [12], Perez-Gonzalez et al analyzed the performance of existing quantization algorithms and proposed the quantization projection (QP) method which couple the effectiveness of QIM scheme and spread spectrum methods. In the basic QP case, the projection function computes a weighted cross-correlation between the length-L watermarked signal y and projection vector b; therefore, for a single transmitted bit, the projection r is such that…”
Section: Conventional Quantization Projection Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…In paper [12], Perez-Gonzalez et al analyzed the performance of existing quantization algorithms and proposed the quantization projection (QP) method which couple the effectiveness of QIM scheme and spread spectrum methods. In the basic QP case, the projection function computes a weighted cross-correlation between the length-L watermarked signal y and projection vector b; therefore, for a single transmitted bit, the projection r is such that…”
Section: Conventional Quantization Projection Approachmentioning
confidence: 99%
“…For the watermarking purpose, w i is chosen to be proportional to a i . It can be shown that under the perceptual constraints, this choice minimizes the probability of error [12]. Then…”
Section: Conventional Quantization Projection Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimum distance decoding corresponds to the maximum likelihood decoder for all the above host pdfs and the specified noise pdf. The bit error probability is calculated as the integral of the equivalent noise Z e = X + Z over the error region R [9]: P e = R f Ze (z e )dz e , where…”
Section: Bit Error Probabilitymentioning
confidence: 99%
“…1 when the switch S is open, the equivalent noise is distributed as f Ze (z e ) ∼ N (0, σ 2 X + σ 2 Z ). Thus, it is possible to express the bit error probability P G e as a function of the host variance by [9]:…”
Section: Bit Error Probabilitymentioning
confidence: 99%